Rancang Bangun Sistem Informasi Pemesanan Makanan Berbahan Baku Kedelai Berbasis Web - Saleh Dwiyatno; Ngatono Ngatono; Ahmad Dedi Jubaedi; Erni Krisnaningsih; Edi Haerullah; Melly Sahrani (Jurnal Ilmiah Sains dan Teknologi, 2025)
The application of information technology in business is important to face increasingly competitive competition. Online ordering is an effective solution in expanding market reach and increasing transaction efficiency. CV. Yoza Parama faces obstacles in marketing and transaction services because it does not yet have a web-based product ordering system. This study aims to design and develop a web-based product ordering system that can provide information needed by consumers. This system is expected to overcome the limitations of distance and time in the ordering process. The urgency of this system lies in its ability to facilitate consumers in placing orders, increase the company's internal efficiency, and enable product marketing with a wider reach. This system will be a strategic tool in strengthening CV. Yoza Parama's position in an increasingly competitive market. This study uses the Prototype development method, which allows system adjustments and improvements based on user feedback.